Design and performance evaluation of a cascade thermoacoustic electric generator with side-branched loudspeaker coupling - Isares Dhuchakallaya; Patcharin Saechan (Results in Engineering)
This study presents the design, optimization, and performance evaluation of a novel cascade thermoacoustic electric generator (TAEG) that integrates a commercially available loudspeaker in a side-branched configuration as the acoustic-to-electric transducer. The cascade thermoacoustic engine combines a standing-wave engine and a traveling-wave engine, arranged linearly, to convert thermal energy into acoustic power, which is then harvested by the loudspeaker alternator. The loudspeaker is strategically positioned at the end of a lateral side-branch tube to facilitate energy extraction. The TAEG employs atmospheric air as the working fluid and utilizes standard pipe components, offering a cost-effective and environmentally sustainable solution for small-scale power generation. Using one-dimensional simulations via DeltaEC, the system is optimized to deliver a peak electrical output of 95.16 W at a frequency of 70.33 Hz, with a matched resistive load of 21.28 Ω, corresponding to a thermal-to-electric conversion efficiency of 8.32 %. Parametric studies reveal that both the position of the side-branched loudspeaker and the external load resistance substantially influence performance. These results underscore the importance of precise acoustic coupling between the engine and the alternator. By integrating cascade thermoacoustic engine with side-branched low-cost loudspeaker for energy extraction, this work advances the development of practical, modular, and scalable thermoacoustic systems for off-grid and sustainable micro-power applications.